WHAT INFLUENCE BUYING IMPULSIVENESS AND COMPULSIVE BEHAVIOUR? STUDY FROM GEN Z ONLINE STREAMERS AT JAVA ISLAND - Yuli Kartika Dewi; I Bagus Yosia Wiryakusuma; Carrissa Belluci; Beatrice Michelle Vallerie; Dewi Mustikasari Immanuel (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
Influence is a word that means in moving a person to do something. The existence of the influence of social information that develops in the world of technology is rapidly accompanied by the influence of social norms that develop among the community to form a mindset that leads to customer behaviour in making purchase decisions. In this study, online buying behaviour was examined as a mediating variable that leads to more simultaneous and stronger compulsive buying among customers. This study involved 126 respondents who actively watched and made purchases through the TikTok and Shopee live streaming methods. The data was processed using Smart-PLS and it was found that there was a positive and significant relationship between information social influence (ISI) and Normative Social Influence (NSI) affecting the mediating variable Online Buying Impulsiveness (OBI). However, NSI does not have a significant effect on dependent variable Compulsive Buying, in contrast to a significant ISI, which affects CB directly. These findings reinforce previous research on the role of Online Buying Behaviour as a mediating variable.